PICES Press, Vol. 19, No. 1, Winter 2011 (North Pacific Marine Science Organization (PICES), 2011)
•2010 PICES Science: A Note from the Former Science Board Chairman (pp. 1-4) •2010 PICES Awards (pp. 5-7) •The First Year of FUTURE: A Progress Report (pp. 8-13) •New Chairmen in PICES (pp. 14-19) •Pacific Ocean Interior Carbon Data Synthesis, PACIFICA, in Progress (pp. 20-23) •2011 PICES Calendar (p. 23) •Ecosystems 2010: Global Progress on Ecosystem-based Fisheries Management (pp. 24-26) •PICES 2010 Rapid Assessment Survey (pp. 27-29) •PICES Workshop on “An Introduction to Rapid Assessment Survey Methodologies for Application in Developing Countries” (pp. 30-31) •The State of the Western North Pacific in the First Half of 2010 (pp. 32-34) •PICES Interns (p. 34) •The State of the Bering Sea in 2010 (pp. 35-37) •The State of the Northeast Pacific in 2010 (pp. 38-40)